2009
DOI: 10.1007/s00259-009-1337-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of 99mTc-MDP SPECT for assessment of mandibular growth: development of normal values

Abstract: (99m)Tc-MDP SPECT provides a quantitative method for assessing mandibular condylar uptake as a reflection of the activity of mandibular growth. The maximum pixel value of a 2-D ROI using external standardization and the right to left ratio of the condylar uptake provide the potential for quantitative evaluation of patients with mandibular asymmetry. These parameters will be further evaluated in an upcoming clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 20 publications
5
33
2
Order By: Relevance
“…Furthermore, the mandibular condyle is a morphologically small structure relative to the SPECT spatial resolution; thus, the radioactivity detected in the condyle is mostly governed by the point spread function of the imaging method rather than by the shape of the condyle. 14 The present results also were confirmed by a previous study using SPECT/CT, which showed that SPECT and SPECT/CT had similar sensitivities (80%). 10 This study has a few limitations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the mandibular condyle is a morphologically small structure relative to the SPECT spatial resolution; thus, the radioactivity detected in the condyle is mostly governed by the point spread function of the imaging method rather than by the shape of the condyle. 14 The present results also were confirmed by a previous study using SPECT/CT, which showed that SPECT and SPECT/CT had similar sensitivities (80%). 10 This study has a few limitations.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, maximum ROIs are not dependent on the position or size of the ROI as long as the maximum count per pixel is within the ROI and therefore are less operator dependent. 13,14 ROC analysis showed that the SPECTaver had the highest AUC of 0.899, which is consistent with a prior study using the same ROI method in which the AUC was 0.866 with the mean ROI method. 8 Moreover, the present study also showed that SPECT/CT and SPECT had similar diagnostic performance in the SPECTaver, SPECTmax, and SPECTCTmax methods (P > .05), but not in SPECTCTaver, which showed a significantly smaller AUC compared with the others (P < .05).…”
Section: Discussionsupporting
confidence: 87%
“…47 Planar scintigraphy using 99m Tc-labeled methylene diphosphate, which distributes according to bone blood flow, can be used to evaluate mandibular growth at 1 time point. In the study by Fahey et al, 47 the mean measured ratio of right:left growth determined from 99m Tc-labeled methylene diphosphate uptake was 0.943 ± 0.116 in a symmetric adolescent population. Pripatnanont et al 48 reported a 4.75% ± 1.91% mean difference in isotope uptake in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] The technetium 99 bone scan results exhibited an increased asymmetric activity in the right TMJ, indicating an active bone process in the right TMJ. In addition to the bone scan, a right posterior open bite and progressively worsening maxillary and mandibular asymmetry allowed a conclusion that the patient had an active right condylar hyperplasia.…”
Section: Report Of Casesmentioning
confidence: 96%